Factors Affecting Back Pain in Pregnant Women in the Third Trimester Literature Review - Murbiah, Murbiah; Panduragan, Santhna Letchmi; Pardi, Kasmahwati; Hassan, Hafizah Che; Husin, Husin (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Introduction: Back pain is caused by pain in the lumbosacral area. The increase in intensity with increasing gestational age results from a shift in the center of gravity and changes in body posture. Back pain from sacroiliac/lumbar can be a long term back pain if not treated efficiently. Material and Methods: Literature review aims to examine more deeply about back pain in pregnant women in the third trimester, there were factors that influenced it by reviewing. Methods literature review by searching on Google Scholar and PubMed. The keyword criteria are